GSK3β Exacerbates Myocardial Ischemia/Reperfusion Injury by Inhibiting Myc. (29th April 2022) - Wen, Cong; Lan, Meide; Tan, Xin; Wang, Xiaobo; Zheng, Zaiyong; Lv, Mingming; Zhao, Xuemei; Luo, Hao; Liu, Yanxu; Wei, Ping; Yue, Rongchuan; Hu, Houxiang; et al.
Abstract : Myocardial ischemia/reperfusion (MI/R) injury is a life-threatening disease with high morbidity and mortality. Herein, the present study is conducted to explore the regulatory mechanism of GSK3 β in MI/R injury regarding cardiomyocyte apoptosis and oxidative stress. The MI/R injury mouse model and hypoxic reoxygenation (H/R) cell model were established. The expression pattern of GSK3 β, FTO, KLF5, and Myc was determined followed by their relation validation. Next, loss-of-function experiments were implemented to verify the effect of GSK3 β /FTO/KLF5/Myc on cardiomyocyte apoptosis and oxidative stress in the MI/R injury mouse model and H/R cell model. High expression of GSK3 β and low expression of FTO, KLF5, and Myc were observed in the MI/R injury mouse model and H/R cell model. GSK3 β promoted phosphorylation of FTO and KLF5, thus increasing the ubiquitination degradation of FTO and KLF5. A decrease of FTO and KLF5 was able to downregulate Myc expression, resulting in enhanced cardiomyocyte apoptosis and oxidative stress. These data together supported the crucial role that GSK3 β played in facilitating cardiomyocyte apoptosis and oxidative stress so as to accelerate MI/R injury, which highlights a promising therapeutic strategy against MI/R injury.